The Effect Of Workload And Work Stress On Employees' Turnover Intention In The Production Department At PT. Yuni Internasional Bogor Regency - Nanda, Putri Dwi; Mulyani, Sri (Transforma Jurnal Manajemen, 2025)
The purpose of this study is to analyze the Effect of Workload and Job Stress on Turnover Intention of Production Employees at PT Yuni International, Bogor Regency, both partially and simultaneously. The method used in this study is quantitative research. The population used in this study were Production Employees at PT Yuni International, Bogor Regency. The sampling technique applied by the author is the saturated sample method, where the entire population of the Production department, amounting to 71 people, was used as a sample. Data collection was carried out through primary data, namely data obtained directly from respondents through distributing questionnaires to 71 Production employees. The results of this study indicate that Workload has a partial effect on Turnover Intention of Production employees at PT Yuni International, Bogor Regency, as evidenced by the t-count value > t-table (4.726 > 1.668). This is also strengthened by the Sig value being smaller than 0.05 (0.001 < 0.05). Job stress has a partial effect on the turnover intention of production employees at PT Yuni International, Bogor Regency, as evidenced by the calculated t value > t table (4.939 > 1.688). This is also reinforced by the Sig value (0.001 < 0.05). Workload and work stress have a simultaneous effect on the turnover intention of production employees at PT Yuni International, Bogor Regency, as evidenced by the calculated F value > F table (22.153 > 3.132), this is also reinforced by the Sig value. smaller than 0.05 (0.001 < 0.05)